Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Konsumen Muslim di Alfamart Cabang Tenggarang Bondowoso - Ristiana; Isti Fadah; Suparman (UPT Penerbitan Universitas Jember, 2025)
This study aims to find out and analyze the factors that affect the purchase decision of Muslim consumers at Alfamart Tenggarang Bondowoso branch. This research was carried out quantitatively by collecting primary data obtained through a google form link distributed to respondents. The population of this study is consumers of Alfamart Tenggarang Bondowoso branch. Meanwhile, for the determination of the sample, the Nonprobability Sampling technique of the Purposive Sampling type was used so that a sample of 115 people was prepared. This study uses a multiple linear regression analysis method with SPSS analysis tools. The results of this study show that promotions and price perspectives affect the purchasing decisions of Muslim consumers at Alfamart Southeast Bondowoso branch. Meanwhile, religiosity, product perspective, and location have no effect on Muslim consumers' purchasing decisions at Alfamart Southeast Bondowoso branch. This result is different from previous research where in previous studies it was stated that all research variables affect consumer purchase decisions. This research provides more specific insights into Muslim consumer behavior at Alfamart Tenggarang Bondowoso branch. The main novelty lies in the discovery of two factors that have a significant influence on purchasing decisions, namely promotion and price perspective.